Perancangan Sistem Pencarian Makanan Khas Bali Menggunakan Pendekatan Ontologi - Gede Verel Aditya Setiabudi; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Bali is renowned for its natural beauty and delicious traditional cuisine, such as ayam betutu and babi guling. Despite numerous online platforms offering Balinese recipes, the information provided is often lacking in detail. Therefore, a new search system with categories such as main ingredients, cooking duration, servings, cooking methods, and types of dishes is needed. Ontology, which represents knowledge explicitly and structurally, can be used to develop a more efficient and targeted search system for Balinese recipes. In this research to build the ontology model, the authors used the Methontology method. Research on building an ontology for a Balinese food search system utilized Protégé 4.2.0 software and SPARQL for data queries. The Methontology method resulted in 13 classes, 5 object properties, 4 data properties, and 64 individuals. Testing was conducted using SPARQL queries to verify the accuracy of the developed ontology.